Transformation of corporate client onboarding procedures through AI-enhanced intelligent recognition and integration systems - Yatsemyrskyi, Lev (Актуальні питання економічних наук, 2026)
In the current context of digital transformation of the economy, the implementation of AI in financial systems often complicates the architecture, creating new sources of risk and management uncertainty. Drawing on nearly 6 years of leadership at Nasdaq as Director of Client Integrations and AI Functionality (2023–2025) for the cloud-native Nasdaq Risk Platform (NRP) in high-frequency trading (HFT) environments, this article clarifies the possibilities and limitations of using AI-enhanced integrations in procedures for connecting corporate clients to high-sensitivity financial systems. The purpose of the article is to substantiate approaches that reduce operational risk, increase the reliability of financial infrastructure, and ensure architectural manageability while achieving practical efficiencies such as 30% faster onboarding and 200% efficiency gains. The research methods are based on a systemic and structural-functional analysis of financial business processes, a comparative analysis of architectural approaches to AI integration, a generalization of corporate onboarding practices across financial institutions, practitioner-derived insights from deploying AI for over 100 institutional clients at Nasdaq, and logical and abstract-analytical methods for forming scientifically sound conclusions and recommendations. Results. It is found that the most significant effect of AI-enhanced integrations is achieved when intellectual components are subordinated to deterministic transactional circuits. It is shown that AI increases the efficiency, speed and accuracy of customer data processing primarily at critical points in the onboarding process. At the same time, uncontrolled scaling of AI leads to increased system complexity, technological dependence of financial institutions on external data providers, algorithms and cloud infrastructure, as well as increased regulatory risks for financial infrastructure operators and responsible persons involved in compliance and operational control processes. It is proven that the key problems of AI-enhanced integrations in financial infrastructure are limited interpretability of model results for internal control and regulatory audit services, latent data and model drift in a dynamic environment, as well as the dependence of financial institutions on external AI service providers, which complicates the management of continuity and responsibility for decisions. Conclusions. It is found that AI in financial infrastructure should be considered a tool for reducing operational risk, rather than an autonomous process management mechanism. It is substantiated that the effective implementation of AI-enhanced integrations is possible provided that the analytical and executive circuits are separated, the model lifecycle management is formalized, and mechanisms for controlled degradation are available. This risk-oriented framework, validated through Nasdaq deployments achieving 99.9% uptime and zero-delay migrations for 400+ drop copy workflows, offers actionable patterns for safe AI adoption in regulated HFT and institutional systems. Prospects for further research include the development of quantitative methods to assess the impact of AI-enhanced integrations on operational risk, the formalization of architectural patterns for the safe use of AI in financial systems, and the analysis of their compliance with new regulatory requirements.